Remarkable Increase in the Prevalence of Overweight and Obesity Among School Age Children in Antalya, Turkey, Between 2003 and 2015 - Gamze Çelmeli; Yusuf Çürek; Zümrüt Arslan Gülten; Mehmet Yardımsever; Mustafa Koyun; Sema Akçurin; İffet Bircan (JCRPE, 2019)

(untitled)
Objective:Childhood obesity (OB) is an acknowledged global problem with increasing prevalence reported around the world. We conducted this study with the aim of determining the local trend in OB and overweight (OW) prevalence in the last decade and to observe the alteration of OB and OW prevalence by age group. An additional aim was to construct new age- and gender-specific body mass index (BMI) reference percentile charts for Turkish children living in the city center of Antalya.Methods:This cross-sectional study included 1687 school aged children. International Obesity Task Force guidelines were used to determine the OB and OW prevalence. OW was defined as a BMI between 85th and 95th percentile, and OB >95th percentile. The data were compared with a previous study carried out in the same region in 2003. The least mean square method was used to construct the BMI reference percentile charts.Results:The prevalence rates for OB and OW were 9.8% and 23.2%, respectively, with a combined OW/OB rate of 33%. OB prevalence was higher in boys than girls (p<0.05). The prevalence of combined OW/OB was highest at age 9-10 years. The prevalence of OB has increased 2.9 times during twelve years in this location.Conclusion:Comparing the current findings with rates of OW and OB in the previous decade, childhood OB in Antalya has reached alarming levels. Urgent measures integrated into the national education system should be taken to prevent OB. In addition more surveillance studies should be planned to show the future trend of OB prevalence nationally.